Organic Fertilizer Making Training as an Effort to Implement Sustainable Organic Farming at the Gudangharjo Paranggupito Wonogiri Farmers Group - Sari, Siti Mardhika; Wiyono; Suprapti, Endang; Budiyono, Agus; Daryanti (Journal of Community Capacity Empowerment, 2025)
This community service activity aims to provide training in making organic fertilizer as a practical step towards implementing sustainable organic farming. This program was implemented for members of the Gudangharjo Farmers Group located in Paranggupito, Wonogiri, an area with significant agricultural potential but limited implementation of organic farming practices. The training focused on the utilization of locally available materials, such as cow dung, rice bran, banana leaves, molasses, and decomposing microbes, to produce high-quality organic fertilizer. The methods used included explanations, demonstrations, and hands-on practice to improve participants' understanding and skills. Participants were introduced to the principles of organic farming, the benefits of organic fertilizer, and the technical steps of making compost, with an emphasis on the right ratio of ingredients, aeration, and moisture management. The results showed an increase in participants' knowledge and motivation to adopt organic fertilizer practices, supported by the availability of raw materials in the area. Participants successfully made organic fertilizer during the training, and follow-up evaluations showed their readiness to apply their knowledge in their farming activities. This program contributes to promoting sustainable farming practices and reducing dependence on chemical fertilizers, in line with efforts to preserve the environment and improve soil health. Future programs are expected to expand the reach of the training to neighboring farmer groups and incorporate advanced techniques for organic fertilizer production.